Effect of Acid Treatment on the Opening of Catalyst Pores - Donatus Setyawan Purwo Handoko (PT FORMOSA CENDEKIA GLOBAL, 2023)
Research on the effect of acid treatment on the opening of the pore mouths on the surface of the zeolite catalyst has been carried out. The preparation of the zeolite catalyst was carried out through the processes of soaking, calcination, oxidation and reduction. Initially, the zeolite was soaked for 3 hours in distilled water, then drained and crushed until its size passed a 100 mesh sieve, followed by a calcination process with nitrogen for 5 hours. Then proceed with oxidation for 3 hours followed by a reduction process for 2 hours with hydrogen. Furthermore, the catalyst was impregnated with Ni from the salt Ni.NO3.6(H2O) After that the catalyst is stored and placed in a desiccator. Then an analysis of the catalyst obtained with AAS was carried out to determine the content of Na, Ca, Fe, Mg and K cations, and the content of Al and Si. Then continued with the analysis of acidity with gravimetric method and continued with analysis with the BET method to determine the specific surface area and pore size distribution. Furthermore, the catalyst is used in the catalytic cracking process at various temperatures